Hypothermic ex situ perfusion of human limbs with acellular solution for 24 hours - Haug, Valentin; Kollar, Branislav; Tasigiorgos, Sotirios; Endo, Yori; Kauke-Navarro, Martin; Safi, Ali-Farid; Veeramani, Anamika; Abdulrazzak, Obada; Bausk, Bruce; Walt, David; Pomahac, Bohdan (Transplantation, 2020)
Background: Machine perfusion (MP) has evolved as a promising approach for the ex situ preservation in organ transplantation. However, the literature on the use of MP in human vascularized composite allografts is scarce. The aim of this study was to evaluate the effects of hypothermic MP with an acellular perfusate in human upper extremities and compare with the current gold standard of static cold storage (SCS). Methods: Six upper extremities were assigned to either MP (n = 3) or SCS (n = 3) conditions for 24 h. MP-extremities were perfused with oxygenated Steen solution at a constant pressure of 30 mm Hg and 10°C. Results: Median total ischemia time was 213 min (range, 127-222 min). Myoglobin, creatine-kinase (CK) showed increased levels at the start of MP (medians: myoglobin: 4377 ng/mL, CK: 1442 U/L), peaking 6 h after perfusate exchange (medians: myoglobin: 9206 ng/mL, CK: 3995 U/L) at timepoint 24. Lactate levels decreased from a median of 6.9-2.8 mmol/L over time. Expression of hypoxia-inducible factor 1-alpha peaked in the SCS-group after 8 h, followed by a decrease. Increased hypoxia-inducible factor 1-alpha expression in the MP group was delayed until 20 h. Perfusion pressure, temperature, and circuit flow were maintained at median of 30.88 mm Hg, 9.77°C, and 31.13 mL/min, respectively. Weight increased 1.4% in the SCS group and 4.3% in the MP group over 24 h. Conclusions: Hypothermic ex situ perfusion with an oxygenated acellular Steen solution may extend the allowable extracorporeal preservation time by a factor of 4-6 compared to SCS and holds promise to be beneficial for vascularized composite allograft recipients and victims of traumatic major limb amputation.
Gesehen am 15.10.2020